Improvement of the functional recovery of the upper limb in hemiplegic patients by the use of the technique of induced stress therapy - Bofosa, Teddy; Kam, Eric; Miangindula, Betty; Nkiama, Constant; Kayembe, Tharcisse (The European Research Journal, 2020)
Objectives: To investigate the effects of the induced stress therapy technique in functional recovery of the upper limb in hemiplegic patients.Methods: We conducted a longitudinal study that consisted in following the evolution of the functional recovery of the upper limbs of 60 hemiplegic subjects of the center for physical disabilities of Kinshasa subjected to a program of induced stress therapy for a period of six months from April 2018 to October 2018. The Fugl Meyer scale and Action Research Arm test allowed us to see the effects of this treatment. The parametric t test of student allowed us to compare the averages before and after the treatment.Results: After 6 months of the study, the results of our cases showed a very significant difference between the mean values of global motor skills scores at Action Research Arm between the beginning (51 ± 21%) and the end of treatment (64 ± 20%; p < 0.05). The difference in mean values at the Fugl Meyer scale was also very significant, both at overall scores and under-scores (p < 0.05). There is a very significant difference between older and younger patients compared to the mean values of their overall scores on the motor and independence scales (p < 0.05).Conclusions: We found that induced stress therapy significantly improved the level of functional recovery and autonomy at the Action Research Arm and Fugl Meyer scales. In addition, this improvement was a little slower in the hand than in the other segments of the upper limb.